The Effect Using Local Jokes Strategies To Improve Students’s Speaking Ability In Secondary Level - Sherlya Maftukha; Ulfatul Ma'rifah (Universitas Muhammadiyah Gresik, 2023)
This paper aims to examine and compare the effects of word-play-based local humor strategies. In learning the speaking skills of EFL students at SMP Muhammadiyah 4 Gresik at the secondary level, in this study, 26 EFL students in classes VII A and VII B at an institution in the city of Gresik, East Java, were asked to become a research group, and they were divided randomly into two groups, namely the group experiments using pun-based local jokes and the control group using cooperative learning strategies based on TGT (Team Games Tournament). Each group contains 13 students. Prior to treatment, all participants took a pre-test, which aimed to ensure the homogeneity of these participants. The treatment for experimental participants, namely local jokes, was then started and continued with post-test speaking with material according to the syllabus. Data were then collected and analyzed through the paired samples T-test and independent samples T-test by comparing the results of the study groups before and after being given treatment and comparing the learning outcomes after being given treatment between groups, and the results then revealed that for students who were given more effective treatment, their scores were significantly higher than those of those who did not use conventional methods. The results of the control class students, who were not given any influence, were then lower than those of the experimental group. Thus, it can be concluded that there are significant differences between the experimental group and the control group in terms of how they are affected by the treatment.